The Quality of Word Choice In The Narrative Compositions of the English Department Students - Sherly Since; Stefanus Laga Tukan; Agustinus Ngadiman (Magister Scientiae, 2013)
This study was an attempt to answer the questions: Are the words used in the compositions of Writing I students specific and appropriate? Are the nouns, adjectives, verbs, and adverbs used in the compositions under study specific and appropriate? The data source of the study was the students’ Writing I final test papers of academic years 2006/2007 (15 papers) and 2008/2009 (15 papers). The results are the words made by the students from both academics are specific and appropriate in which the score is 3. There are 20 essays scored 3 or in good quality, 7 essays with excellent score (4), and 3 essays are scored 2 (fair). The nouns used are specific (good score of 3) while the verbs and the modifiers used are somewhat specific (fair score of 2). All four classwords are used appropriately in which the score is 4 (excellent). Based on the results, it is suggested the EESP authorities include vocabulary section in Writing I syllabus that is treated as equally important as any other elements of Writing. The Writing I lecturers are expected to teach the students to master and use specific and appropriate words. The students themselves are encouraged to enrich their vocabularies by reading books.